Evaluación de la extracción de pigmentos naturales de hoja de tomate riñón (Solanum lycopersicum L.) y flor de diente de león (Taraxacum officinale) para la industria textil. - Alvarez Machado, Veronica Elizabeth (2026)
The textile industry faces significant environmental challenges due to the predominant use of synthetic dyes, which generate water pollution and toxic waste. Therefore, it is necessary to develop alternatives to synthetic dyes based on natural pigments that reduce the environmental impact of dyeing processes. This study aimed to evaluate the extraction of natural pigments from tomato leaf (Solanum lycopersicum L.) and dandelion flower (Taraxacum officinale), and their application in dyeing alpaca fibers. Extraction was performed by cold maceration with 80% methanol and ethanol at a 1:50 (plant:solvent) ratio for 720 hours in the dark, with occasional agitation. To determine the solvent with the highest extraction efficiency, a UV-Vis spectrophotometric absorption analysis was conducted. Based on these results, methanol was selected for the subsequent stages of the process. The obtained extracts were applied to pretreated alpaca fibers using two mordants: alum [KAl(SO₄)₂·12H₂O] and potassium sulfate (K₂SO₄). Dyeing was carried out in thermal baths, and color evaluation was conducted using CIELab parameters and the yellowness index (YI), and morphological characterization was performed using scanning electron microscopy (SEM). Results showed that methanol yielded extracts with higher absorbance, while alum improved color fixation, stability, and homogeneity after washing, compared with potassium sulfate, which showed lower color persistence. In conclusion, natural pigments extracted from tomato leaf and dandelion flower demonstrate potential for use as ecological dyes for protein fibers, representing a sustainable alternative for both artisanal and industrial textile applications.